Burst Mode Q:switched Laser Pulses for Plasma Excitation in LIBS Analysis - Ponce, Luis; Moreira, Lesther; Posada, Eduardo de; Arronte, Miguel; Flores, Teresa; Rodriguez, Eugenio (IntechOpen, 2010)
None